Design and Construction of Portable Oxygen Concentrator using Pressure Swing Adsorption Technology - Bahari, Yunus; Agustina, Sri; Kurniawan, Teguh (ASEAN Journal for Science and Engineering in Materials, 2024)
Oxygen is used in various chemical processes and medical purposes around the world. During the COVID-19 pandemic, the need for medical oxygen has increased sharply in all hospitals in the world. In the current work, we designed anoxygen concentrator by using the Pressure Swing Adsorption (PSA)technology. Efficient operation of the PSA process is required to utilize the adsorbent capacity as much as possible and reduce the processing power requirements. The effect of feed gas temperature, cycle time, and pressure were investigated.  The research is expected to provide suitable operating conditions to develop a better PSA process using zeolite Na-X.